Effect of the indium sulfide phase in CuInS2-TiO2 photocatalysts to boost hydrogen evolution by water splitting - Mizuki Inada; Shizuki Yase; Atsune Tada; Takuma Yamane; Yuki Miyaji; Masanari Hirahara; Yoshiyuki Harada; Syuji Fujii; Takashi Fukushima; Satoru Dohshi; Shinya Higashimoto (Materials Today Catalysis, 2024)
The purpose of this study is to develop a visible light responsive photocatalyst that can remove such environmental pollutants as polysulfide anions and simultaneously generate clean hydrogen energy. An environmentally friendly copper indium sulfide (CuInS2, CIS) nano-colloid was synthesized in aqueous medium for the design of such a photocatalyst. Characterization of the hydrophilic CIS with different In/Cu ratios were studied by XRD, Raman, UV-Vis, photoluminescence spectroscopy. These results showed that the long-lived photoexcited electrons in the CIS with higher In/Cu ratio can be expected to achieve efficient interaction with the reactant molecules. On the photocatalytic activity of CIS, the effect of such various supports as TiO2, and In/Cu ratio of CIS on the reaction promotion was examined. The CIS deposited TiO2 (CIS-TiO2) showed higher photocatalytic activity than bulk CIS, and the indium sulfide-richer CIS-TiO2 showed better performance. The indium sulfide moiety participates in the compensation of the defect sites in the CIS as well as the interaction between In-rich CIS and TiO2 can achieve effective charge carrier separation. This is the first report finding that the indium-richer CuInS2 plays an important role in an improvement of the photocatalytic activity.